Selective laser melting of titanium denture framework - Muhammad Daanish Farhaan Ahmad (2018)
Selective laser melting (SLM) is one of the additive manufacturing (AM) processes that fabricates complicated parts from computer aided design (CAD) data by ‘slicing’ the part and fully melting metallic powders with a high-energy beam. Selective laser melting however is relatively new which results in uncertainty regarding factors such as its process parameters. The focus of this study is to understand the effects of SLM process due to its processing parameters on the dimensional accuracy. Pure titanium is highly suitable for biomedical applications due to its exceptional biocompatibility and is used as the metal powder for SLM. The study of SLM and its complex processing parameters will be further elaborated in the literature review and discussed during the experiment results phase conducted in this study. In this study, SLM printed parts, fabricated using different process parameters, are analysed. The sample was then CT scanned to obtain the ‘projection’ images which were reconstructed into a 3D model of the scanned sample. This image was compared to the original CAD design for any deviations. These were used to analyse the dimensional accuracy which is the main topic of this study of the SLM process on the denture framework and the process parameters that affect these readings. The study found that scan speed and support orientation has a considerable effect on dimensional accuracy. This was observed from the difference in position of cylinders 1 & 4 of the frameworks with different support orientation. Through careful consideration, it is concluded that this is attributed to the thermal stresses that causes warpage. The optimal parameters and effects are clearly stated in this study for future reference.